Quality of Life after Liver Transplantation - Das, Bidhan C; Rahman, Mohammed Mostafizur; Khan, Md Zulfiqur Rahman (Journal of Surgical Sciences, 2019)
We have searched articles published in various journals world wide on quality of life (Qol) after liver transplantation through internet; 38 articles were available through our searching process. After reviewing all papers we have found that there is no transplant specific assessment tool for measuring Qol after liver transplantation. General tools are used for assessment of Qol of these patients. PretransplantationQol are severely affected when compared to normal healthy volunteers. Hepatocellular carcinoma and cholestatic etiologies have higher Qol scores than those related to alcohol or viral hepatitis. Post-transplantation Qol scores are not affected by the etiology of the original liver cirrhosis, but transplant recipient scores continue to remain significant!)'. lower than those of healthy patient controls. The Qol scores improve during initial time after liver transplantation, but decreases in the long term. It may be due to decreases in the physical function and bodily pain domains as the patient's age increases, develops osteoporosis from long-term intake of steroids, and chronic rejection process. It is also addressed that Qol is not good in patients with Hepatitis C after liver transplantation. The development of a Qol assessment tool specific to transplantation could help to more accurately assess factors that alter post-transplantation Qol. Journal of Surgical Sciences (2014) Vol. 18 (2) : 67-77